Effects of changes in the structural parameters of bionic straw sandwich concrete beetle elytron plates on their mechanical and thermal insulation properties. (February 2019) - Zhang, Zhijie; Chen, Jinxiang; Elbashiry, Elsafi Mohamed Adam; Guo, Zhensheng; Yu, Xindi
Abstract: To develop new, environmentally friendly prefabricated building materials, the effects of individual changes in structural parameters on the mechanical and thermal insulation properties of straw sandwich concrete beetle elytron plates (SCBEPs), i.e., sandwich plates with trabeculae constituting the core layer structure, were analyzed by ABAQUS. In addition, based on the analysis results, the structural parameters were preliminarily optimized. The results revealed the following. 1) The bearing capacity of a SCBEP is mainly controlled by deformation (i.e., the maximum deflection). The two most influencing factors on the deflection are the panel thickness T and the trabecular radius R. In contrast, although the panel area is very large, the influence of changing the panel thickness on the thermal insulation performance ranks only third. This demonstrates that the thermal bridge effect of the concrete trabeculae and edges is the primary limitation on further improvements to the thermal insulation performance of SCBEPs. 2) Based on the effects of individual changes in structural parameters on the performance of SCBEPs and their actual processing and application requirements, the structural parameters of a SCBEP with optimized mechanical properties and thermal insulation properties are determined. 3) Compared with aerated concrete wallboards, the optimized SCBEP has a higher rigidity, more compacted surface and better durability. Compared with straw concrete wallboards, the optimized SCBEP has a higher straw content and better thermal insulation performance. Thus, it provides a new avenue for the development of a new, lightweight wallboard. Highlights: Based on BEP, SCBEP has been promoted and the influences of parameters on its properties were investigated by FEM. Optimized SCBEP satisfies the mechanical requirements and its insulation performance is very close to self-insulating wall. The advantages of SCBEPs have been given through comparative analysis with both ﻿aerated concrete and straw concrete wall.